1994
DOI: 10.3109/00365519409087534
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunodetection of malignant solid tumours

Abstract: An increased clinical utility of radiolabelled monoclonal antibodies (MoAb), recognizing a variety of different antigens expressed preferentially in malignant tissue, for localizing primary, metastatic and recurrent cancer has been documented in many recent investigations. This review focuses on both basic and practical aspects of radioimmunodetection in oncology and is a status report on the performance and limitations of radiolabelled antibody procedures currently applied to the clinical detection of maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 81 publications
0
20
0
Order By: Relevance
“…[13] This led to multiple scintigraphic applications. [14] The clinical research in 80's and 90's focused on neurology [15] using various SPECT ligands and on oncology [16] using more than 20 different monoclonal antibodies. Substantial development in 80's was made in cell labeling methods.…”
Section: Editorialmentioning
confidence: 99%
“…[13] This led to multiple scintigraphic applications. [14] The clinical research in 80's and 90's focused on neurology [15] using various SPECT ligands and on oncology [16] using more than 20 different monoclonal antibodies. Substantial development in 80's was made in cell labeling methods.…”
Section: Editorialmentioning
confidence: 99%
“…Due to its relatively low sensitivity and high cost, anti‐melanoma scintigraphy, in spite of its good specificity, did not receive very widespread use. Neither could a significant impact on the management of cancer be documented for the anti‐CEA, ‐CA 125 and ‐CA 19–9 methods tested (Kairemo & Liewendahl, 1994). The radioimmunological methodology is expected to gain new momentum by molecular engineering of antibodies.…”
Section: Nuclear Medicine Research At Helsinki University Hospital 19mentioning
confidence: 99%
“…These include antibodies against prostatic acid phosphatase, prostate-specific antigens and the 7Ell-C5 glycoprotein (34). Some MAbs (34,35). However, there is only one report of treatment of metastatic prostate carcinoma with a radiolabeled antibody.…”
Section: Prostate Cancermentioning
confidence: 99%
“…In patients with cutaneous T-cell lymphoma receiving RIT (10 mg TI01 labeled with 100 mCi of I3lI), plasmapheresis lowered the HAMA titers down to 61% (55). HAMA can cause false-positive CA-125 values in routine CA-125 immunoradiometric assays (IRMA) (35,69). In 32 patients, Baum et al (69) found a HAMA frequency of 34% (11/32: 3/17 after the first administration, 6/13 after the second, and 2/2 after the third).…”
Section: Ha M a Responsementioning
confidence: 99%